2023
DOI: 10.2147/jhc.s408819
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Drug-Eluting Bead Transarterial Chemoembolization Combined with Lenvatinib and Anti-PD-1 Antibodies for Unresectable Hepatocellular Carcinoma: A Retrospective Analysis

Abstract: Background Drug-eluting bead transarterial chemoembolization (DEB-TACE) has good efficacy in the treatment of unresectable hepatocellular carcinoma (uHCC), with a relatively high objective response rate (ORR) compared to conventional transarterial chemoembolization (cTACE). This study aimed to evaluate the safety and medium-term clinical efficacy of DEB-TACE combined with lenvatinib (LEN) plus PD-1 inhibitors as a triple therapy for the treatment of uHCC. Methods Data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
(79 reference statements)
0
4
1
Order By: Relevance
“…The differences in the results might be attributed to different baseline characteristics among the studies. For example, the proportions of patients with BCLC stage C (54.3%) and extrahepatic metastasis (8.6%) in Wu et al’s study 29 was significantly lower compared to those observed in our study, and these features were associated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…The differences in the results might be attributed to different baseline characteristics among the studies. For example, the proportions of patients with BCLC stage C (54.3%) and extrahepatic metastasis (8.6%) in Wu et al’s study 29 was significantly lower compared to those observed in our study, and these features were associated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 84%
“… 11 , 32 In addition to camrelizumab and sintilimab, other ICIs such as tislelizumab, pembrolizumab, and toripalimab have also been used in similar studies. 19 , 29 However, the optimal drug regimen for advanced HCC remains uncertain in real-world practice due to the heterogeneity of this tumor, and our study provided new insights into multi-drug combination therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All 12 subgroups of studies reported the conversion rate and ORR, whereas 11 subgroups from nine studies reported the DCR, and eight studies provided data on the incidence of grade ≥3 AEs. Regarding the treatment strategies, three subgroups adopted LEN + LRT ( 12 , 25 , 39 ) and nine subgroups adopted LEN + ICI + LRT ( 12 , 24 26 , 45 49 ). Among the nine studies that used TACE, two utilized drug-eluting bead TACE ( 39 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
“…Local treatments, such as transarterial chemoembolization (TACE), induce tumor necrosis, exposing a large amount of tumor antigen and initiating the immune response cycle[ 21 , 22 ]. In a study involving patients diagnosed with unresectable HCC, the combination of lenvatinib (anti-VEGF) and PD-1 inhibitors after drug-eluting bead TACE (DEB-TACE) resulted in higher objective response rates and surgical conversion rates[ 23 ].…”
Section: Introductionmentioning
confidence: 99%